The Role of insurance in disaster risk reduction and resilient rebuilding: a case study of the 2017 Knysna fires - Dube, Sabelo Renaissance (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.